FENOMENA MUTASI ATLET MENJELANG PELAKSANAAN PEKAN OLAHRAGA NASIONAL XVII - Saharuddin Ita (University of Cenderawasih, 2013)
Abstrack: Mutation athlete phenomenon pre PON XVII. Porpuse this research for fine data about mutation athlete phenomenon Pre PON XVII, the research race is descriptive research . subject research is management KONI provinsi, top organization sport propinsi, coach, and athlete whose prepare to PON XVII at Kalimantan timur. Take sampling used quota purposive stratified sampling with technic focus group discussion, questionnaire, and document. Conclusion : (1) athlete mutation pre PON constitute a phenomenon accomplished fact because domicile, education, job, following wife/husband and parent; (2) mutation is rightful authority athlete and sport organization must responship; (3) infraction of rule mutation, because athlete or sport organization. Sanction pattern is athlete unallowable appear on PON; (4) prestation at PON not endall to athlete. Mutation must be compensation to development of relationship for province; (5) mutation have to impact athlete prosperity, compensation to development from province athlete destination, must can be development to management province, management regency, so this compensation must until to club; (6) athlete mutation have positif impact to self athlete but not yet to coach.Key word: Mutation Athlete, PON